2021
DOI: 10.1038/s41598-021-81744-0
|View full text |Cite|
|
Sign up to set email alerts
|

The lengths of trachea and main bronchus in Chinese Shanghai population

Abstract: The knowledge of airway length is the theoretical basis in the diagnosis and management of airway disease. The objective of this study is to measure the length of trachea and left and right main bronchus in Chinese Shanghai population. A total of 153 consecutive adult patients with minor pulmonary disease in Xinhua hospital were enrolled for bronchoscopy examination. Measurements were conducted on head and neck neutral position and height, weight and age for each patient were recorded either. Student t test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
5
1
1
Order By: Relevance
“…Similarly, we did not investigate the difference between 3D imaging and bronchoscopy measurement. Although bronchoscopy is a preoperative examination for TRR, measuring the tracheal length from the vocal cord to the carina using bronchoscopy is different from 3D imaging measurement ( 29 ). Last, the usefulness of data regarding the tracheal length in TRR remains unclear, since there are no data on the tracheal length of patients who underwent TRR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we did not investigate the difference between 3D imaging and bronchoscopy measurement. Although bronchoscopy is a preoperative examination for TRR, measuring the tracheal length from the vocal cord to the carina using bronchoscopy is different from 3D imaging measurement ( 29 ). Last, the usefulness of data regarding the tracheal length in TRR remains unclear, since there are no data on the tracheal length of patients who underwent TRR.…”
Section: Discussionmentioning
confidence: 99%
“…± 14.59 yrs. [3]. Our patient has a measured trachea length of 11.7 cm from vocal cords to carina and 11.1 cm from vocal cords to the mainstem bronchi as measured by radiographical imaging.…”
Section: Discussionmentioning
confidence: 86%
“…Various methods have been described for accurate tube positioning including age, height, and ETT internal diameter (ID). Other study have shown that the length of trachea may vary according to gender 25 . Moreover, weight can be the independent variable for the length of the orotracheal tube in previous study 26 .…”
Section: Methodsmentioning
confidence: 94%